Locus of control and its relationship to prejudice attitudes among Tafila Technical University students’ - Al-Qaisi, Saida Hamad; Thawabieh, Ahmed Mahmoud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the locus of control and its relationship to prejudiced attitudes among the students of Tafila Technical University. To achieve the objectives of the study, two scales were developed: the locus of control scale and the prejudice attitudes scale. The verification of their psychometric characteristics was confirmed. The study sample consisted of 750 male and female students from all university colleges. A descriptive analytic approach was used. The study concluded that the mean for locus of control and prejudiced attitudes was mid, and the external control center was more common among students of Tafila Technical University, the predictive ability of the locus of control on prejudiced was statistically significant, And there were statistically significant differences in the internal control center dimension depending on the variable of gender and college and the interaction between them, and the differences tended to favor females, and the results showed no statistically significant differences in the external control center dimension depending on the gender and college variable. The differences in the total degree in prejudiced attitudes that attributed to the college were statistically significant in favor of the scientific colleges, also the interaction between the sex and college in favor of females of the scientific colleges. Based on the results the study recommended the necessity of providing students with psychological programs and workshops to reduce the level of external control to reduce Prejudice Attitudes.